Focal cortical dysplasia: Etiology, epileptogenesis, classification, clinical presentation, imaging, and management - Tahta, Alican; Turgut, Mehmet (Springer, 2020)
Background Focal cortical dysplasia (FCD) is the most prevalent cause of intractable epilepsy in children. It was first described by Taylor et al. in 1971. In 2011, the International League against Epilepsy described an international consensus of classification for FCD. However, the exact mechanism causing this pathology remains unclear. The diagnosis and recognition of FCD increase with the advances in neuroradiology and electrophysiology. Focus of review In this paper, we discuss the literature regarding management of FCD with a focus on etiology, pathophysiology, classification, clinical presentation, and imaging modalities. We will also discuss certain variables affecting surgical outcome of patients with FCD. Conclusion Based on our review findings, it is concluded that surgical management with complete resection of the lesion following preoperative localization of the epileptogenic zone in patients with FCD subtypes can provide a seizure-free outcome.
Keywords: Epilepsy; Focal Cortical Dysplasia; Outcome; Surgery